Collective bargaining as a tool to ensure a living wage. Experiences from the Nordic countries. (August 2019) - Alsos, Kristin; Nergaard, Kristine; Van Den Heuvel, Andreas
To date the Nordic countries have not had a public debate on living wages, in contrast to many Anglo-Saxon countries. This does not mean, however, that the concept of a living wage is alien to them. In this article we examine whether wage-setting mechanisms in the Nordic countries promote and secure a living wage for all employees, and how trade unions have approached the concept of a living wage.